Sol-gel synthesized nanomaterials for environmental applications - Yang, Xiangxin (Kansas State University, 2008)
Over the past decade, nanomaterials have been the subject of enormous interest. Their defining characteristic is a very small size in the range of 1-100 nm. Due to their nanometer size, nanomaterials are known to have unique mechanical, thermal, biological, optical and chemical properties, together with the potential for wide-ranging industrial applications. Here, we synthesized nanocrystalline metal oxides through the sol-gel process and used these materials as desulfurization adsorbents and photocatalysts. Deep desulfurization of fuels has received more and more attention worldwide, not only because of health and environmental consideration but also due to the need for producing ultra-low-sulfur fuels, which can only be achieved under severe operating conditions at high cost using hydrodesulfurization (HDS). Consequently, development of new and affordable deep desulfurization processes to satisfy the decreasing limit of sulfur content in fuels is a big challenge. Sol-gel derived Cu/Al[subscript]2O[subscript]3 and Zn/Al[subscript]2O[subscript]3 adsorbents have been demonstrated to be effective in the removal of thiophene from a model solution. Results showed that Cu[superscript]+ was the active site and thermal treatment under vacuum was critical for Zn/Al[subscript]2O[subscript]3 since a defective, less crystalline spinel led to stronger interaction between zinc ions and thiophene molecules in the adsorption process. The kinetic study suggested that most of the adsorption occurred in the first 30 min, and adsorption equilibrium was attained after 1.5 h. Both adsorbents showed good regenerative property. TiO2 is considered the most promising photocatalyst due to its high efficiency, chemical stability, non-toxicity, and low cost for degradation and complete mineralization of organic pollutants. However, the use of TiO[subscript]2 is impaired because it requires ultraviolet (UV) activation ([Lambda]<387 nm). The shift of optical response of TiO[subscript]2 from the UV to the visible light region would have a profound positive effect on the efficient use of solar energy in photocatalytic reactions. We shifted the optical response of TiO[subscript]2 and improved the photocatalytic efficiency through size modification and transition metal ion and nonmetal atom doping. Experimental results showed that C and V co-doped TiO[subscript]2 catalysts had much higher activity than commercial P25 TiO[subscript]2 towards the degradation of acetaldehyde under visible light irradiation. For the first time, we reported that activities were comparable in the dark and under visible light irradiation for co-doped TiO[subscript]2 with 2.0 wt% V. C and N co-doped TiO[subscript]2 exhibited higher activity for the degradation of methylene blue than pure TiO[subscript]2 under visible light and UV irradiation. Possible mechanisms were discussed based on the experimental results.
Keywords: nanomaterial; environment; sol-gel; sorbent; photocatalyst; Chemistry, General (0485); Energy (0791); Engineering, Chemical (0542); Engineering, Environmental (0775); Engineering, Industrial (0546); Engineering, Materials Science (0794); Engineering, Petroleum (0765); Environmental Sciences (0768)